Mothers and Others: Promoting Healthy Living Through Research - Letherby, Gayle (Atlantis, 2008)
This article considers how women and girls - whether they mother biologically related children or not - are affected by the often contradictory ideologies of motherhood and consider the relationship between non/motherhood and un/healthy living. It considers some of the ways to further promote healthy living for mothers and others.